Influence of residual stress on the adhesion and surface morphology of PECVD-coated polypropylene. (6th October 2017) - Jaritz, Montgomery; Hopmann, Christian; Behm, Henrik; Kirchheim, Dennis; Wilski, Stefan; Grochla, Dario; Banko, Lars; Ludwig, Alfred; Böke, Marc; Winter, Jörg; Bahre, Hendrik; Dahlmann, Rainer
Abstract: The properties of plasma-enhanced chemical vapour deposition (PECVD) coatings on polymer materials depend to some extent on the surface and material properties of the substrate. Here, isotactic polypropylene (PP) substrates are coated with silicon oxide (SiO x ) films. Plasmas for the deposition of SiO x are energetic and oxidative due to the high amount of oxygen in the gas mixture. Residual stress measurements using single Si cantilever stress sensors showed that these coatings contain high compressive stress. To investigate the influence of the plasma and the coatings, residual stress, silicon organic (SiOCH) coatings with different thicknesses between the PP and the SiO x coating are used as a means to protect the substrate from the oxidative SiO x coating process. Pull-off tests are performed to analyse differences in the adhesion of these coating systems. It could be shown that the adhesion of the PECVD coatings on PP depends on the coatings' residual stress. In a PP/SiOCH/SiO x -multilayer system the residual stress can be significantly reduced by increasing the thickness of the SiOCH coating, resulting in enhanced adhesion.